Influence of partial oxidation of xanthate on flotability of gold minerals - Daulet, B.Ye.; Turysbekov, D.K.; Semushkina, L.V.; Narbekova, S.M.; Kaldybayeva, Zh.A.; Mukhamedilova , A.M. (Chemical Bulletin of Kazakh National University, 2026)
Losses of gold minerals with fine grades remain an urgent problem of modern flotation technology. Gold minerals associated with iron sulfides (pyrite, arsenopyrite) can be extracted using sulfhydryl collectors. As it is known, the maximum flotability of iron sulfides is observed in case of simultaneous presence on their surface of both xanthate and dixanthogen. The aim of the work is to study the effect of partial oxidation of amyl potassium xanthate (AKs) on the efficiency of flotation enrichment of gold-bearing sulfide ore. Partial oxidation of potassium amyl xanthate solution using turboflotation generator is proposed to obtain a collector including xanthate and dixanthogen in its composition. Testing of collectors AKs and AKs + AKsokisil. on sulfide gold-bearing ore showed that partial oxidation of xanthate to dixanthogen improves technological indicators of flotation. Partial oxidation of xanthate allows to increase gold recovery from 83.8 to 89.3 % at reduction of gold content in flotation tailings from 0.48 to 0.32 g/t. Turboflotation generator allows to increase gold recovery from 89.2 to 91.7 % at reduction of gold content in flotation tailings from 0.31 to 0.24 g/t.